The Logistics Handbook: A Practical Guide for the Supply Chain Management of Health Commodities (John Snow, 2015)
Supply chain managers and others will learn about a wide range of logistics principles and practices. Tie objectives listed at the beginning of each chapter will guide you in selecting chapters of particular interest. By reading only the main body text, you will learn the basic principles of logistics management. Tie handbook highlights each function of the logistics cycle, in detail, as well as describes other necessary logistics system principles, including assessing stock status, inventory control, and system design.